The Magic of One Lyric Theme in Marina Tsvetaeva’s Works of 1921-1925. - GEVORGYAN, TATYANA (Bulletin of Yerevan University H: Russian Philology, 2021)
The article sums up the analysis of the lyric theme shone through M.Tsvetaeva’s collections “Craft” (“Remeslo”) and “After Russia” (“Posle Rossii”), as well as in five works of large form in 1921-1925. This lyric theme was considered by the author previously in a series of papers, and the present article observes the same lyric subject in relation with two Tsvetaeva’s references to goodness Aphrodite; that is the challenge to goodness in ironic cycle “Praise of Aphrodite” at the beginning and the revenge of goodness at the end (tragedy “Ariadna”, planned as the first of trilogy “The Ire of Aphrodite”).